1985
DOI: 10.1161/01.atv.5.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle cells produce an inhibitor of endothelial cell growth.

Abstract: A potent inhibitor of endothelial cell growth and neovascularization has previously been isolated from both bovine and human aorta. In an attempt to determine if the major cellular component of that tissue, smooth muscle cells, synthesized molecules with this activity, we studied the effects of serum-free conditioned medium from bovine aortic smooth muscle on the growth of cultured endothelial cells from bovine aorta. The smooth muscle conditioned medium was found to contain both growth inhibitory and stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Our data demonstrating, in SMC conditioned medium, a nonfilterable inhibitory activity for EC proliferation are consistent with that of Schumacher et al 6 who described a 35 to 40 K dalton peptide in bovine aortic SMC conditioned medium that inhibits growth of proliferating EC. Other investigators have noted briefly that media of cultured SMC from calf pulmonary artery 12 and bovine aorta 1314 stimulate bovine aortic EC 1213 or bovine capillary EC 14 growth in vitro, but the nature of these activities has not been described further.…”
Section: ±29supporting
confidence: 93%
See 2 more Smart Citations
“…Our data demonstrating, in SMC conditioned medium, a nonfilterable inhibitory activity for EC proliferation are consistent with that of Schumacher et al 6 who described a 35 to 40 K dalton peptide in bovine aortic SMC conditioned medium that inhibits growth of proliferating EC. Other investigators have noted briefly that media of cultured SMC from calf pulmonary artery 12 and bovine aorta 1314 stimulate bovine aortic EC 1213 or bovine capillary EC 14 growth in vitro, but the nature of these activities has not been described further.…”
Section: ±29supporting
confidence: 93%
“…Other investigators have noted briefly that media of cultured SMC from calf pulmonary artery 12 and bovine aorta 1314 stimulate bovine aortic EC 1213 or bovine capillary EC 14 growth in vitro, but the nature of these activities has not been described further. Schumacher et al 6 described an EC growth stimulator in whole conditioned medium of bovine aortic SMC as heat labile, but we found that our EC growth-promoting substance, separated from the inhibitor by urtrafiltratjon, was retained after boiling even with visible loss of other materials as precipitates. This EC growth stimulator had a molecular weight less than 1000 daltons, was stable to extremes in pH, was not degraded by trypsin, and was completely stable to repeated freezing and thawing.…”
Section: ±29mentioning
confidence: 55%
See 1 more Smart Citation
“…Though several EC growth factors have been described including an acidic (Lemmon et al, 1982;Gordon et al, 1983;Maciag et al, 1984a) and a basic (Gospodarowicz et al, 1976(Gospodarowicz et al, , 1983 form of fibroblast growth factor, EC growth factor (Maciag et al, , 1984b, and several other acidic mitogens (Barritault et al, 1982;D'Amore and Klagsbrun, 19841, most laboratories successfully culture arterial EC in plasma-or serum-containing media without further supplementation. Several growth inhibitors specific for EC have been reported (Heimark and Schwartz, 1985;Schumacher et al, 1985), including one that is a membrane component of confluent but not subconfluent EC (Heimark and Schwartz, 1985). The mechanism of action of these growth inhibitors has not yet been determined.…”
mentioning
confidence: 99%